A homochiral vanadium–salen based cadmium bpdc MOF with permanent porosity as an asymmetric catalyst in solvent-free cyanosilylation. Issue 7 (1st December 2015) - Bhunia, Asamanjoy; Dey, Subarna; Moreno, José María; Diaz, Urbano; Concepcion, Patricia; Van Hecke, Kristof; Janiak, Christoph; Van Der Voort, Pascal
Abstract : This chiral framework shows the highest H2 adsorption and CO2 capacity for currently known salen-based MOFs and shows an excellent performance as an asymmetric catalyst in solvent-free cyanosilylation. Abstract : A homochiral vanadium–salen based MOF with thepcu topology is constructed via in situ synthesis under solvothermal conditions. The synthesized MOF exhibits BET surface areas of 574 m 2 g −1, showing the highest H2 adsorption capacity (1.05 wt% at 77 K, 1 bar) and the highest CO2 uptake (51 cm 3 g −1 at 273 K, 1 bar) for currently known salen-based MOFs. This framework shows excellent performance as an asymmetric catalyst in solvent-free cyanosilylation.